STRATEGI PENCEGAHAN TERORISME MELALUI PENDIDIKAN KARAKTER DAN LITERASI DIGITAL DI KALANGAN REMAJA - Mahesa Dharma Huda; Agung Gunawan Pertama Putra (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze strategies for preventing terrorism among adolescents through character education and digital literacy approaches. The method used is a literature review by examining various sources such as journals, books, official reports, and government regulations related to radicalism prevention. The findings indicate that character education integrating values of tolerance, empathy, nationalism, and morality can shape anti-violence attitudes among youth. Strengthening digital literacy, including fact-checking, information verification, and critical thinking, plays an essential role in countering terrorist propaganda in digital spaces. Collaboration among schools, families, communities, and technology-based strategies such as educational content and digital campaigns are effective efforts to prevent youth radicalization. This study is expected to serve as a reference for developing more comprehensive and applicable terrorism prevention programs.